Efficiency of Aqueous Extract of Clitoria ternatea L. in controlling Aphis craccivora Koch, 1854 (Aphididae) and Chalcodermus bimaculatus Fiedler, 1936 (Curculionidae) in Cowpea - José Lucas Queiroz Lucena; José Maria Arcanjo Alves; Ammabel Costa Lopes; Natália Ribeiro Almada; Sandra Lima Cruz; Deyse Cristina de Oliveira Silva; Musibau Oyeleke Azeez (Agro@mbiente On-line)
The cultivation of cowpea (Vigna unguiculata (L.) Walp.) is limited by pests such as the black aphid (Aphis craccivora Koch, 1854) and the pod weevil, commonly known as manhoso (Chalcodermus bimaculatus Fiedler, 1936), which significantly reduce productivity and compromise the quality of harvested grains. Within the context of Integrated Pest Management (IPM), the use of plant extracts has been increasingly recognized as a promising alternative to conventional chemical control, with a lower environmental impact. This study aimed at evaluating the effectiveness of an aqueous extract of Cunhã (Clitoria ternatea L.) in controlling these two pests in cowpea cultivation. The experiment was conducted using the UFRR-Grão Verde cultivar, in a completely randomized design with three treatments: Control - water application), Evidence® 700WG insecticide - IMIDACLOPRID 700 g kg-1, 150 g p.c. ha-1; 500 L ha-1 of spray solution, and aqueous extract of Cunhã - 100 g L-1 of water, fresh weight basis, with varying replications. Cowpea rows (9 m) were alternated with strips of Brachiaria ruziziensis (9 m), spaced at 0.8 m apart, used as living barriers between treatments. Applications were carried out at 18, 30, and 46 days after planting (DAP). At 62 DAP, when the pods were physiologically matured, 20 pods per plot were collected to assess the incidence of C. bimaculatus. The extract of Cunhã treatment was effective in controlling A. craccivora, reducing infestation, but was ineffective against C. bimaculatus. The Evidence® 700WG insecticide treatment satisfactorily controlled both pests, demonstrating its effectiveness as the reference chemical treatment.